Myths and Misconceptions of Airway Pressure Release Ventilation: Getting Past the Noise and on to the Signal - Andrews, Penny; Shiber, Joseph; Madden, Maria; Nieman, Gary F.; Camporota, Luigi; Habashi, Nader M. (Frontiers in Physiology, 2022)
In the pursuit of science, competitive ideas and debate are necessary means to attain knowledge and expose our ignorance. To quote Murray Gell-Mann (1969 Nobel Prize laureate in Physics): “Scientific orthodoxy kills truth”. In mechanical ventilation, the goal is to provide the best approach to support patients with respiratory failure until the underlying disease resolves, while minimizing iatrogenic damage. This compromise characterizes the philosophy behind the concept of ‘lung protective’ ventilation. Unfortunately, inadequacies of the current conceptual model – that focuses exclusively on a nominal value of low tidal volume and promotes shrinking of the ‘baby lung’ - is reflected in the high mortality rate of patients with moderate and severe acute respiratory distress syndrome. These data call for exploration and investigation of competitive models evaluated thoroughly through a scientific process. Airway Pressure Release Ventilation (APRV) is one of the most studied yet controversial modes of ventilation that shows promise in experimental and clinical data. Over the last three decades APRV has evolved from a rescue strategy to a preemptive lung injury prevention approach with potential to stabilize the lung and restore alveolar homogeneity. However, several obstacles have so far impeded the evaluation of APRV’s clinical efficacy in large, randomized trials. For instance, there is no universally accepted standardized method of setting APRV and thus, it is not established whether its effects on clinical outcomes are due to the mode per se or the method applied. In addition, one distinctive issue that hinders proper scientific evaluation of APRV is the ubiquitous presence of myths and misconceptions repeatedly presented in the literature. In this review we discuss some of these misleading notions and present data to advance scientific discourse around the uses and misuses of APRV in the current literature.